Long breathing lean NOx trap regeneration with supplemental n-butanol. (February 2019) - Aversa, Christopher; Yu, Shui; Jeftić, Marko; Bryden, Geraint; Zheng, Ming
This paper evaluates a long breathing strategy of lean NO x trap for achieving ultra-low nitrogen oxide (NO x ) emissions, with an aim to reduce the associated fuel penalty. The fuel impacts on the long breathing strategy of lean NO x trap operation are examined on a heated flow bench with diesel and n -butanol as the reductants. Engine tests are performed to identify suitable working regions for the lean NO x trap strategies. For a very low engine-out NO x emission level of ~30 ppm, the long breathing adsorption of the lean NO x trap shows a significant improvement in NO x storage efficiency compared to a conventional lean NO x trap operational strategy for a moderate level of NO x emissions. The use of n -butanol fuel in diesel engines produces much lower NO x and particulate matter emissions, which is deemed advantageous for operating the long breathing lean NO x trap strategy. As a reductant for lean NO x trap regeneration, n -butanol is found to be more effective in terms of regeneration effectiveness, NO x conversion efficiency, and potential hydrogen (H2 ) yield compared to using diesel fuel in the after-treatment. A fuel penalty analysis is conducted for the selected cases with combinations of different combustion modes and lean NO x trap strategies. Given a low level of NO x emissions from n -butanol combustion, the long breathing lean NO x trap strategy can potentially achieve ultra-low NO x emissions with a minimum fuel penalty.